AI-POWERED PRONUNCIATION TOOLS: SUPPORTING ENGLISH LEARNERS IN MULTILINGUAL CLASSROOMS WHO DISLIKE ENGLISH IN PONTIANAK - Amanda Nurul Hidayah; Dwi Riyanti; Etna Gres; Yohanes Gatot Sutapa Yuliana (Universitas Wiralodra, 2025)
This study explores the role of AI-powered pronunciation tools in supporting English learners in multilingual classrooms, focusing on 7th-grade students at Pelita Cemerlang School in Pontianak who express a dislike for learning English. The study aims to explore learners’ experiences and perceptions of these tools, particularly how they influence motivation and engagement in pronunciation practice. A qualitative descriptive design was employed, with interviews conducted with a sample of 20 participants to gather in-depth insights. The findings suggest that AI-powered pronunciation tools provide personalized feedback that helps students identify and correct pronunciation errors, making the learning process more interactive and engaging. For instance, students reported noticeable improvements in their ability to produce challenging sounds and patterns. However, the tools were found to be most effective when complemented by traditional teacher-led instruction. The study concludes that AI-driven technologies can play a valuable role in pronunciation practice for students with low motivation, though their integration into the classroom should consider diverse learner needs and preferences.